Influence of geochemical processes on geotechnical stability of tailings storage facilities - Orcutt, Heath Marie, author; Scalia, Joseph, IV, advisor; Bareither, Christopher, advisor; Ridley, John, committee member (Colorado State University. Libraries, 2023)
Incorporation of geochemically induced material changes and weathering patterns into geotechnical design and long-term stability analyses of tailings storage facilities has yet to be implemented widely or consistently. Tailings are deposited in disequilibrium with the surrounding environment and must undergo physical, chemical, and biological weathering to reach their most stable form. As a result, the geotechnical properties of the tailings (i.e., particle size, water retention capacity, shear strength, etc.) change over time. Herein, an in-depth review of published literature is provided, ranging across multiple disciplines (geochemistry, geotechnical engineering, hydrogeology, environmental engineering, mining engineering), and focusing on studies that document or allude to material property changes of weathered sulfidic base metal tailings. Synthesized visual aids are provided as a framework for beginning interdisciplinary conversation that couples geochemistry and geotechnical engineering. By drawing attention to potential geochemically induced failure modes, I hope to draw connections between geochemistry and geotechnical engineering that are fundamental to developing robust designs and advanced monitoring plans that ensure long-term tailings storage facility stability. A "proof of concept" laboratory design is presented which analyzes changes to the physical material properties (compressibility, permeability, and shear strength) of saturated fine-synthetic tailings mixed with calcite at different pH values. Overall, this report seeks to lay the foundation for future study and advance communication between experts.
Keywords: geotechnical stability; weathering; tailings; geochemistry